Parthenope’s Embodiment of Victory and the Crowning of Acheloios as ‘Victor over Death’: A Reconsideration of the Reverse Motif Exhibited on Neapolitan Coinage - Molinari, Nicholas J. (KOINON: The International Journal of Classical Numismatic Studies, 2022)
The nymphs are truly marvelous figures of antiquity, and utterly pervasive, too. In Larson’s work, she records the name of some 426 of them, many of which (like meliai, ash tree nymphs) denote a group of such figures. Numbers like these give us a clear quantitative indication of just how essential the nymphs are to Greek culture. They operate in a liminal function mediating between the human and divine; they are therapeutic, and communion with the nymphs was often sought after in antiquity; their femininity is alluring and yet they are wildly unpredictable; they are always fixed to a specific water source from which their powers derive; and, they tend to exist in many multiples, often maintaining a general anonymity. Perhaps most importantly of all, they function as auxiliaries in the process of metempsychosis and often accompany psychopomps in ancient art. It is primarily for these reasons, and because Acheloios is often referred to as their father, that, within the pages of POΤΑΜΙKOΝ, Dr. Sisci and I advocated a somewhat controversial —or at least seemingly counterintuitive—claim, namely, that the winged figure crowning Acheloios Sebethos on the coinage of Neapolis was not Nike, but rather a chthonic nymph. Here we loosely followed the works of Kurt Regling, Ettore Gabrici, Maria Caccamo Caltabiano, and Grazia Salamone, all of whom questioned the seemingly unequivocal identification of winged female figures on coinage from Magna Graecia and Sicily with Nike, and in doing so advocated for some form of polysemy, or the idea that multiple meanings are conjoined in the iconography and this type of syncretism would have been apparent to the ancient observer. Dr. Sisci and I went so far as to relabel many of these ‘Nike’ figures as winged, chthonic nymphs, doing away with the Nike dimension entirely, since an Acheloios-nymph pairing made more sense within the Acheloian cultic context.